Increased Cu(II) Adsorption Onto UV-Aged Polyethylene, Polypropylene, and Polyethylene Terephthalate Microplastic Particles in Seawater - Han, Xiaoxin; Vogt, Rolf D.; Zhou, Jiaying; Zheng, Boyang; Yu, Xue; Feng, Jianfeng; Lu, Xueqiang (Frontiers in Marine Science, 2021)
Environmental effects of microplastic are rather due to their adsorption capacity of contaminants than themselves. Aging is a key factor influencing adsorption properties of environmental microplastics. In order to clarify this influence, polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) microplastics with particle sizes of <0.9 mm, 0.9–2 mm, and 2–5 mm were artificially aged in seawater for 12 months. This enabled an assessment of the change in Cu(II) adsorption capacity to the microplastics particles under aging. According to the FTIR spectra, fresh microplastics were oxidized during the UV induced aging process. The adsorption capacities of microplastic were positively correlated with their aging time. After 12-months aging, the amount of Cu(II) adsorbed to the aged microplastics was 1.45–2.92 times higher than on the fresh microplastic particles. For PP and PET, the aging effect increased with decreasing size of the microplastic particles. In the case of PE, particles with the medium particle size (0.9–2 mm) had the strongest aging effect.